GROWTH AND AVAILABLE NUTRIENT IN WINTER MAIZE (ZEA MAYS L.) WITH VEGETABLE INTERCROPS IN EASTERN UTTAR PRADESH - S. K. CHOUDHARY; R. N. SINGH; P. K. UPADHYAY; R. K. SINGH; R. I. YADAV; H. R. CHOUDHARY (The Bioscan, 2013)
A field experiment was conducted during the winter season in the years 2010-2011 at agriculture research farm the Banaras Hindu University, Varanasi. To find out the production potential and nutrient status of winter maize (Zea mays L.) intercropped with various vegetable like radish (Raphanus sativus) spinach (Spinacia oleracea L.) and carrot (Daucus carota). Values of plant height (209.99cm), no of active leaves (10.90) and plant dry matter (171.02 g plant-1) at 120 DAS and cob height (95.49 cm), grain yield of maize (69.99 q ha-1) significantly greater in sole crop than the intercropping systems, and days to 50% tasseling (110.50), days to 50% silking (117.0) and barren on plants plot-l (1.70), maize equivalent yield (282.46 q ha-1) was significantly higher in intercrops than the sole maize crop. Result also revealed that association of carrot with maize crop improved availability of residual nitrogen, phosphorous and potassium.